Metastatic Niches and the Modulatory Contribution of Mesenchymal Stem Cells and Its Exosomes - Valenzuela Alvarez, Matias Juan Pablo (2019)
Mesenchymal stem cells (MSCs) represent an interesting population due to their capacity to release a variety of cytokines, chemokines, and growth factors, and due to their motile nature and homing ability. MSCs can be isolated from dierent sources, like adipose tissue or bone marrow, and have the capacity to dierentiate, both in vivo and in vitro, into adipocytes,chondrocytes, and osteoblasts, making them even more interesting in the regenerative medicinefield. Tumor associated stroma has been recognized as a key element in tumor progression, necessary for the biological success of the tumor, and MSCs represent a functionally fundamental part of this associated stroma. Exosomes represent one of the dominant signaling pathways within the tumor microenvironment. Their biology raises high interest, with implications in dierent biological processes involved in cancer progression, such as the formation of the pre-metastatic niche. This is critical during the metastatic cascade, given that it is the formation of a permissive context that wouldallow metastatic tumor cells survival within the new environment. In this context, we explored the role of exosomes, particularly MSCs-derived exosomes as direct or indirect modulators. All this points out a possible new tool useful for designing better treatment and detection strategies for metastatic progression, including the management of chemoresistance.